Patch-clamp fluorometry–based channel counting to determine HCN channel conductance - Liu, Chang (J Gen Physiol, 2016)
Counting ion channels on cell membranes is of fundamental importance for the study of channel biophysics. Channel counting has thus far been tackled by classical approaches, such as radioactive labeling of ion channels with blockers, gating current measurements, and nonstationary noise analysis. Here, we develop a counting method based on patch-clamp fluorometry (PCF), which enables simultaneous electrical and optical recordings, and apply it to EGFP-tagged, hyperpolarization-activated and cyclic nucleotide–regulated (HCN) channels. We use a well-characterized and homologous cyclic nucleotide–gated (CNG) channel to establish the relationship between macroscopic fluorescence intensity and the total number of channels. Subsequently, based on our estimate of the total number of HCN channels, we determine the single-channel conductance of HCN1 and HCN2 to be 0.46 and 1.71 pS, respectively. Such a small conductance would present a technical challenge for traditional electrophysiology. This PCF-based technique provides an alternative method for counting particles on cell membranes, which could be applied to biophysical studies of other membrane proteins.